Positive Health Outcomes Associated with Live Microbe Intake from Foods, Including Fermented Foods, Assessed using the NHANES Database - Hill, Colin; Tancredi, Daniel J; Cifelli, Christopher J; Slavin, Joanne L; Gahche, Jaime; Marco, Maria L; Hutkins, Robert; Fulgoni, 3rd, Victor L; Merenstein, Daniel; Sanders, Mary Ellen (The Journal of nutrition, 2023)
Live dietary microbes have been hypothesized to contribute to human health but direct evidence is lacking. This study aimed to determine whether the dietary consumption of live microbes is linked to improved health outcomes. Data from the NHANES 2001-2018 were used to assess microbial intake and their adjusted associations with selected physiological parameters (e.g., blood pressure, anthropometric measures, and biomarkers) among adults aged 19 y and older. Regression models were constructed to assess the microbial intake with each physiological parameter and adjusted for demographics and other covariates. Microbial intake was assessed as both a continuous variable and a 3-level categorical variable. Fermented foods were assessed in a separate model. In continuous models, an additional 100-g intake of microbe-containing foods was associated with a lower systolic blood pressure (regression coefficient: -0.331; 95% CI: -0.447, -0.215 mm Hg), C-reactive protein (-0.013; 95% CI: -0.019, -0.008 mg/dL), plasma glucose -0.347; 95% CI: -0.570, -0.124 mg/dL), plasma insulin (-0.201; 95% CI: -0.304, -0.099 μU/mL), triglyceride (-1.389; 95% CI: -2.672, -0.106 mg/dL), waist circumference (-0.554; 95% CI: -0.679, -0.428 cm), and BMI -0.217; 95% CI: -0.273, -0.160 kg/m ) levels and a higher level of high density lipoprotein cholesterols (0.432; 95% CI: 0.289, 0.574 mg/dL). Patterns were broadly similar when microbial intake was assessed categorically and when fermented foods were assessed separately. To our knowledge, this study is the first to quantify, in a nationally representative data set of American adults and using stable sets of covariates in the regression models, the adjusted associations of dietary intakes of live microbes with a variety of outcomes, such as anthropometric measures, biomarkers, and blood pressure levels. Our findings suggest that foods with higher microbial concentrations are associated with modest health improvements across a range of outcomes.